Biaxially oriented polyethylene terephthalate film roll

By applying specific stretching conditions and surface orientation control, biaxially oriented polyester film rolls can be produced from recycled PET materials with high foreign matter content, addressing productivity and durability issues while promoting environmental sustainability.

JP7666712B2Active Publication Date: 2025-04-22TOYOBO CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024104400
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-06-27
Publication Date
2025-04-22
Estimated Expiration
2041-09-01

AI Technical Summary

Technical Problem

Existing technologies face challenges in producing biaxially oriented polyester films using recycled PET materials contaminated with foreign matter, leading to reduced productivity and film durability.

Method used

The use of specific stretching conditions and surface orientation control for biaxially oriented polyethylene terephthalate film rolls, even when made from recycled PET materials with high foreign matter content, to achieve desired thermal shrinkage rates, surface orientation coefficients, and foreign object presence.

Benefits of technology

This approach results in environmentally friendly, long-lasting, and high-productivity biaxially oriented polyester film rolls, capable of incorporating significant amounts of recycled materials without compromising film integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666712000005
    Figure 0007666712000005
  • Figure 0007666712000006
    Figure 0007666712000006
  • Figure 0007666712000001
    Figure 0007666712000001
Patent Text Reader

Abstract

To provide a film roll produced by winding a biaxially oriented polyester film, where the film employs a recycled material derived from a PET container, can be produced with satisfactory productivity in a longer shape without being broken even when a large amount of foreign matter is contained in the recycled material, and is friendly to the global environment.SOLUTION: Provided is a biaxially oriented polyethylene terephthalate film roll produced by winding a biaxially oriented polyethylene terephthalate film into a roll, where the film employs a recycled material derived from a PET container and satisfies (1) to (3) in the following: (1) the thermal shrinkage in the film length direction as measured at 150°C for 30 minutes is from 0.5% to 2.0% inclusive; (2) the plane orientation coefficient (ΔP) of the film calculated from a refractive index measured in accordance with the JIS K 7142-1996 A method is from 0.16 to 0.17 inclusive; and (3) the number of foreign bodies whose maximum length is 1.3 mm or more is 1 or more per 1000 m2 of the film roll.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biaxially oriented polyethylene terephthalate film roll obtained by winding a biaxially oriented polyester film into a roll shape. More specifically, the present invention relates to a biaxially oriented polyester film roll that uses recycled raw materials from PET containers, is environmentally friendly, has good film formability even when using recycled raw materials from PET containers that contain a lot of foreign matter, and has excellent productivity. [Background technology]

[0002] Aromatic polyesters, such as polyethylene terephthalate (PET), have excellent mechanical properties and chemical resistance, and are widely used as molded products such as fibers and films. PET resins in particular are inexpensive and hygienic, and are therefore widely used as food and beverage containers. In recent years, with growing environmental concerns and the need to conserve resources, used PET containers have long been recycled, and methods for their utilization are attracting attention.

[0003] In addition, by using recycled materials from PET bottles, CO 2 It is said that this will also lead to reductions, and from the perspective of the global environment, there is a desire to increase the use of recycled materials from PET containers, even if only as much as possible.

[0004] Recycled raw materials from PET containers are made by collecting A-PET, which is used in PET bottles for beverages and containers for salads and vegetables. However, since the recycled raw materials are made from waste that has been released into the market, the amount of foreign matter contained in the raw materials is higher than that of PET raw materials derived from fossil fuels. Therefore, the biaxially oriented polyester film obtained has a high number of breaks caused by foreign matter, which leads to a problem of reduced productivity. The foreign matter referred to here refers to substances other than PET resin, such as the band labels and gravel of PET bottles, and chemicals such as pesticides and insecticides that consumers have filled into PET bottles. In order to suppress breaks caused by foreign matter, there is a method of forming a film by passing the molten resin through a filter with high filtration accuracy. By this method, foreign matter is sufficiently removed, so breaks caused by foreign matter are reduced, but clogging occurs due to the accumulation of foreign matter in the filter. Therefore, the filter needs to be replaced at an early cycle, which results in a decrease in productivity. In addition, there is a method of gradually removing foreign matter by using filters with different mesh sizes multiple times, but this method lengthens the melting line and reduces the molecular weight of the recycled raw material, which ultimately leads to a decrease in the mechanical strength of the resulting biaxially oriented polyester film. On the other hand, the problem of foreign matter can be solved by selecting only clean, unsoiled PET containers from the collected PET containers and using them as recycled raw materials. However, it is bad for the environment if dirty PET containers cannot be recycled.

[0005] Patent Document 1 discloses a biaxially oriented polyester film made from recycled PET bottle materials. In Patent Document 1, the filter back pressure rise coefficient of the recycled materials is suppressed to the same level as that of PET materials derived from fossil fuels, and the obtained biaxially oriented polyester film also has little foreign matter. However, if only clean PET containers are selected and used after collection, the environmental effects are insufficient. In addition, even if a sufficient filtration process is carried out when producing the recycled materials, the filter replacement cycle will be shortened, and productivity is expected to decrease. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2014-65282 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0007] The present invention has been made against the background of the problems of the conventional technology. That is, the object of the present invention is to provide a film roll made by winding up a biaxially oriented polyester film, which is a film made from recycled raw materials derived from PET containers, and which has good productivity and can be made into a long film without breaking even if the recycled raw materials contain a large amount of foreign matter, and is environmentally friendly. [Means for solving the problem]

[0008] As a result of extensive research, the inventors have discovered that even when using recycled raw materials derived from PET containers as the raw material, by selecting a specific range of stretching conditions and controlling the degree of planar orientation of the film, the productivity of the obtained film can be good and it can be made into a long length without breakage even if the recycled raw materials contain a large amount of foreign matter, and have arrived at the present invention.

[0009] That is, the present invention comprises the following: [1] A biaxially oriented polyethylene terephthalate film roll made by using recycled raw materials from PET containers and winding up a biaxially oriented polyethylene terephthalate film that satisfies the following (1) to (3) into a roll. (1) The thermal shrinkage rate in the longitudinal direction of the film when measured at 150°C for 30 minutes is 0.5% or more and 2.0% or less. (2) The plane orientation coefficient (ΔP) of the film calculated from the refractive index measured based on JIS K 7142-1996 Method A is 0.16 or more and 0.17 or less. (3) 1000m film roll 2 There is one or more foreign objects with a maximum length of 1.3 mm or more per unit. [2] The biaxially oriented polyethylene terephthalate film roll according to [1], characterized in that the recycled raw material derived from the PET container described in [1] is a mechanically recycled polyester resin and / or a chemically recycled polyester resin. [3] The biaxially oriented polyethylene terephthalate film roll according to [1] or [2], characterized in that the thickness variation per 800 mm in the film width direction is 18% or less. [4] The biaxially oriented polyethylene terephthalate film roll according to any one of [1] to [3], characterized in that the breaking strength in the longitudinal direction of the film is 180 MPa or more and 260 MPa or less, and the breaking elongation is 80% or more and 170% or less. [5] Film roll 8000m 2 The biaxially oriented polyethylene terephthalate film roll according to any one of [1] to [4], characterized in that the number of foreign objects having a maximum length of 1.0 mm or more per roll is 16 or more. [6] The biaxially oriented polyethylene terephthalate film roll according to any one of [1] to [5] above, having a roll length of 10,000 m or more. Effect of the Invention

[0010] The biaxially oriented polyester film roll of the present invention uses recycled raw materials derived from PET containers as the raw material, and by controlling the thermal shrinkage rate in the longitudinal direction of the film, the planar orientation coefficient (ΔP), and the number of foreign matter within predetermined ranges, a biaxially oriented polyester film roll that is environmentally friendly and has good productivity and can be produced in long lengths even if the recycled raw materials contain a large amount of foreign matter can be obtained. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a schematic diagram showing a logarithmic pattern TD stretching method in the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing a TD stretching method of a multistage stretching pattern in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. The recycled raw material derived from PET containers preferably used in the present invention is mainly composed of polyethylene terephthalate, and the shape of the container from which it is recycled is not limited, and it may contain a small amount of coloring components. In the following, polyester resin recycled from PET bottles will be used as an example for explanation, but the present invention is not limited thereto.

[0013] [Polyester resin made from recycled PET bottles] As the polyester resin in the present invention made by recycling PET bottles, either a polyester resin obtained by a physical regeneration method in which used PET bottles collected from the market or society are sorted, crushed, and washed to thoroughly remove surface dirt and foreign matter, and then exposed to high temperatures to thoroughly wash away contaminants remaining inside the resin, and then the bottles are pelletized again (hereinafter, this may be referred to as a mechanically recycled polyester resin) or a polyester resin obtained by decomposing polyester resin contained in used packaging containers to the monomer level, removing contaminants, and polymerizing the decomposed resin again (hereinafter, this may be referred to as a chemically recycled polyester resin) can be suitably used.

[0014] The biaxially oriented polyester film of the present invention preferably uses polyester resin recycled from the market or society, including PET bottles, as described below. By using polyester resin recycled from the market or society, including PET bottles, the ratio of recycled raw materials in the film can be increased, making it possible to obtain an environmentally friendly film. The polyester resin recycled from the market or society, including PET bottles, used in the biaxially oriented polyester film of the present invention is mainly made of recycled containers mainly made of polyethylene terephthalate. For example, recycled beverage containers for tea drinks, soft drinks, etc. can be preferably used. They may be appropriately oriented, and are preferably colorless, but may contain a small amount of coloring components.

[0015] The recycled raw material from PET containers preferably used in the present invention is a polyester produced and molded by a normal polymerization method or a solid-phase polymerization method, preferably composed mainly of polyethylene terephthalate, and may contain other polyester components and copolymer components. It may also contain metal compounds such as antimony, germanium, and titanium as catalysts, and phosphorus compounds as stabilizers.

[0016] Germanium is often used as a catalyst in polyester for regular PET bottles, and if recycled PET bottle materials are used to make a film, the film will contain more than 1 ppm of germanium. However, since this is merely the catalyst content, it is usually no more than 100 ppm, and usually no more than 50 ppm.

[0017] Hereinafter, mechanically recycled polyester resin and chemically recycled polyester resin will be described.

[0018] [Mechanically recycled polyester resin] The collected used recycled PET bottles are sorted to avoid mixing with other materials or garbage, and after removing the labels, they are crushed into flakes. These flakes often contain foreign matter attached to them. In addition, it is possible that consumers fill used PET bottles with chemicals such as medicines and solvents and use them. For example, detergents for dishes, insecticides, herbicides, agricultural chemicals, and various oils are possible. Since normal washing cannot sufficiently remove the chemicals adsorbed on the surface of the PET bottles, it is preferable to perform alkaline washing. As the alkali metal hydroxide solution used in this washing process, a sodium hydroxide solution or a potassium hydroxide solution is used. In such a washing process, a preliminary washing may be performed before the alkaline washing. If alkaline washing is not performed, these will remain as foreign matter in the raw resin, which will not only cause contamination and lead to breakage during film production and reduce productivity, but will also remain as foreign matter in the film, affecting the appearance of the film and causing printing defects in the subsequent printing process.

[0019] The concentration of the aqueous solution of alkali metal hydroxide used in the washing step varies depending on the temperature, time, and stirring state, but is usually in the range of 1 to 10% by weight. The time required for washing is in the range of 10 to 100 minutes, and it is preferable to carry out the washing with stirring to enhance the effect.

[0020] It is preferable to perform rinsing and drying after the alkali washing. The alkali washing and rinsing may be repeated several times. If the aqueous solution of alkali metal hydroxide used in the washing in the alkali washing step remains in the flakes, the properties of the film finally obtained may be affected by the subsequent melt extrusion step in the pelletizing step or the melt extrusion step during film formation.

[0021] The sodium and potassium concentrations in the film finally obtained using polyester resins recycled from the market or society, including these PET bottles, are preferably greater than 0 ppm and less than 150 ppm, more preferably 3 to 120 ppm, and even more preferably 5 to 80 ppm. If the sodium or potassium concentration in the film is higher than 150 ppm, the film's heat resistance and thermal stability will decrease and it will become discolored, which is undesirable. If there is no sodium or potassium in the film, the effect of suppressing the production of diethylene glycol will be reduced, which is undesirable. In addition, polyester resins recycled from the market or society, including PET bottles, may contain a small amount of these components, and it is difficult to eliminate them completely.

[0022] In such a washing process, the PET bottle flakes are partially hydrolyzed by the aqueous solution of alkali metal hydroxide. In addition, the degree of polymerization of the resin decreases due to the heating during the molding of the PET bottles. Furthermore, after the collected PET bottles are crushed for reuse, the degree of polymerization decreases due to the influence of heat and moisture when melting and pelletizing again. They can be reused as they are, but depending on the application, if the degree of polymerization decreases, the moldability, strength, transparency, heat resistance, etc. may be deteriorated, and they may not be able to be reused as they are.

[0023] In such a case, in order to restore the reduced degree of polymerization, it is preferable to perform solid-state polymerization on the crushed and washed PET bottle flakes or on the flakes which have been melted and pelletized.

[0024] In the solid-state polymerization step, the washed flakes, or the flakes melt-extruded and pelletized, can be subjected to continuous solid-state polymerization in an inert gas such as nitrogen gas or a rare gas at 180 to 245°C, preferably 200 to 240°C.

[0025] It is desirable to adjust the flake or pellet conditions so that the final polyester resin recycled from the market or society, including PET bottles, has an intrinsic viscosity of 0.55 to 0.90 dl / g, preferably 0.60 to 0.85 dl / g.

[0026] The process for pelletizing the flakes will now be described. The flakes are melted, extruded, cooled, and pelletized using an extruder having a degassing means and a filtering means.

[0027] The melting step in the extruder can be carried out by melt kneading at a temperature of usually 260 to 300°C, preferably 265 to 295°C. The flakes obtained by crushing the PET bottles to be fed must be sufficiently dried, and it is preferable to dry them under conditions where the moisture content is 5 to 200, preferably 10 to 100 ppm, and further 15 to 50 ppm. If the flakes contain a large amount of moisture, a hydrolysis reaction will proceed in the melting step, and the intrinsic viscosity of the resulting polyester resin will decrease. As a degassing means, it is preferable to have at least one vacuum vent in the melting zone of the resin.

[0028] The extruder preferably has a filter as a filtering means capable of filtering out solid foreign matter having a particle size of 25 μm or more, preferably 15 μm or more, more preferably 10 μm or more, from the molten resin.

[0029] The molten resin that has passed through the filter passes through a die and is cooled in water, after which it is cut into pellets of the desired shape and granulated. [Polyester resin composition] The biaxially oriented polyester film of the present invention is made of a polyester resin composition containing the following polyester resin as a main component. The polyester resin constituting the biaxially oriented polyester film of the present invention is a polymer synthesized from a dicarboxylic acid or its ester-forming derivative and a diol or its ester-forming derivative. Examples include polyethylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate, and polyethylene terephthalate is preferred from the viewpoints of mechanical properties, heat resistance, cost, etc. The term "main component" as used herein means that the content in the polyester resin composition is 80% by weight or more, preferably 90% by weight or more, more preferably 95% by weight or more, and most preferably 98% by weight or more.

[0030] In addition, these polyester resins may be copolymerized with other components as long as the object of the present invention is not impaired. Specifically, the copolymerization components include dicarboxylic acid components such as isophthalic acid, naphthalenedicarboxylic acid, 4,4-diphenyldicarboxylic acid, adipic acid, sebacic acid and their ester-forming derivatives. In addition, the diol components include diethylene glycol, hexamethylene glycol, neopentyl glycol, and cyclohexanedimethanol. In addition, polyoxyalkylene glycols such as polyethylene glycol and polypropylene glycol are also included. The copolymerization amount is preferably 10 mol% or less per constituent repeating unit, more preferably 5 mol% or less, and most preferably 3 mol% or less.

[0031] The lower limit of the filter back pressure increase coefficient when the recycled raw material derived from the PET container of the present invention is melt extruded at a temperature of 285°C, a filter filtration diameter of 20 μm, and a filtration rate of 6 g / min is preferably 10 MPa / kg cm 2 and more preferably 20 MPa / kg cm 2 and particularly preferably 30 MPa / kg cm 2 It is. The filter back pressure increase coefficient referred to here indicates the resistance of a filtration filter to clogging when a resin is melt-extruded, and is calculated by the following formula. K = ΔP / (Q / S) Where, K is the filter back pressure increase coefficient, ΔP=P1-P0 P1: Pressure after 4 hours of extrusion (MPa), P0: Pressure at the start of extrusion (MPa), Q: Extrusion discharge rate (kg / hr), S: Filter filtration area (cm 2 )

[0032] The filter back pressure increase coefficient during melt extrusion under the above conditions is 10MPa / kg cm 2 By exceeding the above standards, it is meant that the PET containers are essentially recycled raw materials with no sorting required, and this provides sufficient environmental benefits. The upper limit of the filter back pressure increase coefficient when the recycled raw material derived from PET containers of the present invention is melt extruded at a temperature of 285°C, a filter filtration diameter of 20 μm, and a filtration rate of 6 g / min is preferably 100 MPa / kg cm 2 and more preferably 90 MPa / kg cm 2 and 80 MPa / kg cm is particularly preferred. 2 100MPa / kg cm 2 By setting the above, the productivity can be improved simply by adjusting the production conditions of the biaxially oriented polyester film.

[0033] [Chemically recycled polyester resin] The method for producing the chemically recycled polyester resin used in the present invention is not particularly limited, but specifically, for example, as described in JP-A-2000-169623, collected used PET bottles are sorted, crushed, washed to remove foreign matter, and then depolymerized to decompose them into raw materials or intermediate raw materials for PET resin, which are then purified and polymerized to produce new PET resin. Depolymerization includes a method in which ethylene glycol (EG) is added in the presence of a catalyst to return the intermediate raw material in resin production to bis-2-hydroxyethyl terephthalate (BHET), which is an intermediate raw material, and then purified and repolymerized into PET, and a method in which polyethylene terephthalate is heated in a non-aqueous organic solvent in the presence of a catalyst containing oxidized iron as an essential component to produce terephthalic acid and ethylene glycol, which are then polymerized again, as described in JP-A-2000-302707. The characteristic of chemically recycled polyester resin is that foreign matter and other materials are removed during the depolymerization / repolymerization process, allowing it to be regenerated into a polyester resin of the same high quality as virgin resin. This makes it more hygienic than the mechanically recycled polyester resin described above, making it particularly suitable for use in food packaging.

[0034] The chemically recycled polyester resin used in the present invention is made from bales of compressed used PET bottles. These PET bottle bales are produced by known methods currently adopted by municipalities. Other polyethylene terephthalate waste or flakes of PET bottles can be used as starting materials instead of PET bottle bales.

[0035] A PET bottle bale made by compressing PET bottle waste to reduce its volume is placed in a crusher, and hot water, room temperature water, or hot water or room temperature water containing detergent is poured in to crush the PET bottles underwater.

[0036] Next, the mixture of flakes of PET bottles and washing water discharged from the crusher is immediately subjected to gravity separation to separate the metal, stone, glass, sand and flakes.The flakes are then separated from the washing water, rinsed with ion-exchanged water and centrifuged for dehydration.

[0037] The crude polyethylene terephthalate flakes obtained in the above pretreatment step are depolymerized, melted and simultaneously hydrolyzed to give a polyethylene terephthalate melt with a low degree of polymerization, which is then depolymerized with an excess of ethylene glycol to give a two-component mixed solution of crude BHET and crude ethylene glycol.

[0038] After the depolymerization reaction is completed, the temperature of the mixture of crude BHET and crude ethylene glycol is lowered and the mixture is filtered to remove unreacted linear and cyclic oligomers as high melting point precipitates, coagulation of remaining foreign plastics other than polyethylene terephthalate, and solid foreign matter such as metals. The mixture is then subjected to adsorption and ion exchange treatment to remove colored matter and dissolved ions, thereby removing the foreign matter contained in the crude BHET.

[0039] The mixed solution of crude BHET and crude ethylene glycol obtained through the pre-purification step is subjected to distillation and evaporation operations to separate and distill off ethylene glycol to obtain concentrated BHET, or the mixed solution of the two is cooled to 10°C or less to crystallize BHET, and then the ethylene glycol and BHET are subjected to solid-liquid separation to obtain concentrated BHET, and this concentrated BHET is evaporated in vacuum at a temperature of more than 190°C and not more than 250°C at a residence time of the concentrated BHET in an evaporator of 10 minutes or less to obtain purified bis-β-hydroxyethyl terephthalate.

[0040] After the high purity purified BHET is obtained as described above, the purified BHET is charged into a melt polycondensation reactor to obtain a high purity polyethylene terephthalate polymer.

[0041] Among the polyester resins constituting the biaxially oriented polyester film of the present invention, examples of a method for producing a polyester resin derived from a fossil fuel other than a mechanically recycled polyester resin or a chemically recycled polyester resin include a method in which the above-mentioned dicarboxylic acid or its ester-forming derivative and a diol or its ester-forming derivative are used as main starting materials, and the resulting polyester resin is then subjected to an esterification or ester exchange reaction according to a conventional method, and then subjected to a polycondensation reaction at high temperature and reduced pressure.

[0042] The intrinsic viscosity of the polyester resin constituting the biaxially oriented polyester film of the present invention is From the viewpoints of film-forming property and re-collection property, the range of 0.50 to 0.90 dl / g is preferable, and more preferably The range of 0.55 to 0.80 dl / g is preferred.

[0043] The biaxially oriented polyester film of the present invention may contain, in addition to the polyester resin composition, conventionally known additives such as lubricants, stabilizers, colorants, antioxidants, antistatic agents, and ultraviolet absorbing agents.

[0044] When the entire biaxially oriented polyester film of the present invention is taken as 100% by mass, the content of the polyester resin composition is preferably 99.5% by mass or more, more preferably 99.6% by mass, and most preferably 99.7% by mass.

[0045] The lubricant can adjust the dynamic friction coefficient of the film, and examples of the lubricant include inorganic lubricants such as silica, calcium carbonate, alumina, and organic lubricants. Silica and calcium carbonate are preferred, and from the viewpoint of achieving both transparency and lubricity, porous silica is the most preferred.

[0046] The lower limit of the lubricant content in the biaxially oriented polyester film of the present invention is preferably 100 ppm by mass, more preferably 300 ppm by mass, and most preferably 500 ppm by mass. By making it 100 ppm by mass or more, the lubrication property of the film can be improved. The upper limit of the lubricant content in the biaxially oriented polyester film of the present invention is preferably 10000 ppm by mass, more preferably 6000 ppm by mass, and most preferably 2000 ppm by mass. By setting it to 10000 ppm by mass or less, the transparency of the film can be made good.

[0047] [Manufacturing method of biaxially oriented polyester film] The method for obtaining the biaxially oriented polyester film of the present invention is not particularly limited, and may be appropriately selected from the T-die method, the inflation method, and the like.

[0048] The film of the present invention may have a single layer structure of at least one layer, or may have a laminate structure of two or more layers, and may also have two, three, four or five layers.

[0049] The upper limit of the cooling roll temperature is preferably 40° C., and more preferably not more than 20° C. When the temperature is 40° C. or higher, the crystallinity of the molten polyester resin composition when cooled and solidified is not too high, making it easier to stretch the composition, and also making it possible to suppress a decrease in transparency due to crystallization. The lower limit of the temperature of the cooling roll is preferably 0° C. If the temperature is 0° C. or higher, the crystallization suppression effect when the molten polyester resin composition is cooled and solidified can be sufficiently exhibited. In addition, when the cooling roll temperature is in the above range, it is preferable to lower the humidity of the environment near the cooling roll to prevent condensation.

[0050] The thickness of the unstretched sheet is preferably in the range of 15 to 2500 μm, more preferably 600 μm or less, and most preferably 400 μm or less.

[0051] Next, the stretching method will be described. The stretching method can be either simultaneous biaxial stretching or sequential biaxial stretching.

[0052] The lower limit of the stretching temperature in the longitudinal direction (hereinafter also referred to as MD direction) is preferably 90° C., more preferably 100° C., and particularly preferably 110° C. If the temperature is 110° C. or higher, the stretching stress can be reduced, and therefore breakage due to foreign matter can be suppressed. The upper limit of the MD stretching temperature is preferably 140° C., more preferably 130° C., and particularly preferably 120° C. If the temperature is 140° C. or less, the stretching stress increases due to crystallization, and as a result, not only can breakage due to foreign matter be suppressed, but also the mechanical strength of the film is improved.

[0053] The lower limit of the stretching ratio in the MD direction is preferably 2.5 times, more preferably 2.8 times, and particularly preferably 3.1 times. When it is 2.5 times or more, not only the mechanical strength of the film is improved, but also the thickness unevenness is improved, leading to improved winding quality when the film is made into a roll. The upper limit of the MD stretching ratio is preferably 4.0 times, more preferably 3.8 times, and particularly preferably 3.6 times. When the stretching ratio is 4.0 times or less, the stretching stress can be reduced, and therefore breakage due to foreign matter can be suppressed.

[0054] It is preferable that a relaxation step in the MD direction is performed between the stretching step in the MD direction and the subsequent stretching step in the transverse direction (hereinafter also referred to as the TD direction). The lower limit of the MD relaxation rate is preferably 1%, more preferably 3%, and particularly preferably 5%. When it is 1% or more, the amorphous components in the film are relaxed, and the stretching stress in the subsequent TD stretching process can be reduced, and as a result, breakage due to foreign matter can be suppressed. The upper limit of the MD relaxation rate is preferably 10%, more preferably 8%, and particularly preferably 6%. When it is 10% or less, wrinkles due to shrinkage can be suppressed, and not only can the quality of the film be improved, but also a decrease in mechanical strength due to orientation relaxation can be suppressed. The method of MD relaxation is not particularly limited, but an example thereof is a method in which a relaxation treatment is carried out by utilizing the speed difference between rolls after heating with a hot air heater.

[0055] The lower limit of the TD stretching temperature is preferably 90° C., more preferably 100° C., and particularly preferably 110° C. If the temperature is 110° C. or higher, the stretching stress can be reduced, and breakage due to foreign matter can be suppressed. The upper limit of the stretching temperature in the TD direction is preferably 140° C., more preferably 130° C., and particularly preferably 120° C. If the temperature is 140° C. or less, the stretching stress increases due to crystallization, and as a result, not only can breakage due to foreign matter be suppressed, but the mechanical strength of the film is also improved.

[0056] The lower limit of the stretching ratio in the TD direction is preferably 2.5 times, more preferably 3.0 times, and particularly preferably 3.5 times. When it is 2.5 times or more, not only the mechanical strength of the film is improved, but also the thickness unevenness is improved, leading to improved winding quality when the film is made into a roll. The upper limit of the TD stretching ratio is preferably 5.0 times, more preferably 4.5 times, and particularly preferably 4.0 times. When the stretching ratio is 5.0 times or less, the stretching stress can be reduced, and therefore breakage due to foreign matter can be suppressed.

[0057] The stretching pattern in the TD direction is preferably logarithmic or multi-stage stretching. Specifically, as shown in Figures 1 and 2, the logarithmic TD stretching pattern is a TD stretching pattern in which the film is stretched more in the first half of the stretching and stretched more slowly in the second half of the stretching, as opposed to a normal linear pattern. By using such a TD stretching pattern, most of the stretching can be completed in the first half where the film stretching stress is low, and the stretching stress applied during stretching can be reduced. As a result, breakage due to foreign matter can be suppressed.

[0058] Next, details of the case where a logarithmic TD stretching pattern is adopted will be described. As mentioned above, a logarithmic TD stretching pattern refers to a TD stretching pattern in which the stretching is large in the first half of the stretching and is gentle in the second half of the stretching. If the number of TD stretching zones is N and the stretching angle in the Nth stretching area is θN, the stretching in the width direction is performed under the condition that the stretching angle in each stretching zone is θn>θn+1. (When θn=θn+1, the stretching is performed in a normal straight line.) The amount of change in the stretching angle when the stretching angle changes from θn to θn+1 can also be appropriately selected to obtain the desired performance. However, when the angle change rate expressed by {(θn-θn+1) / θn}×100 (unit: %) is greater than 50%, it is necessary to extremely increase the stretching ratio at the beginning of TD stretching in order to stretch to a predetermined maximum ratio, so that the stretching stress at the beginning of stretching becomes too large, which may adversely deteriorate the film formability. When the angle change rate is 0%, θ1=θ2, which is the same as the stretching conditions in a conventional tenter, so when a logarithmic TD stretching pattern is adopted, the angle change rate is preferably in the range of 0.5% to 50%, more preferably in the range of 1% to 30%, and particularly preferably in the range of 1.5% to 20%. By setting the stretching angle in the logarithmic TD stretching pattern within the above range, most of the stretching can be completed in the first half where the film stretching stress is low, and the stretching stress applied during stretching can be reduced. As a result, breakage due to foreign matter can be suppressed.

[0059] Next, we will discuss multistage stretching in TD. Multistage stretching involves two or more stages of stretching compared to the usual one-stage stretching, and it is possible to reduce the stretching stress during TD stretching. As a result, it is possible to suppress breakage due to foreign matter.

[0060] The TD multistage stretching is preferably 2 to 5 stage stretching. By using multistage stretching, it is possible to change the stretching temperature and the stretching stress in each stage, and it is preferable to lower the stretching stress during TD stretching. As shown in Fig. 2, in multistage stretching, it is preferable to use a temperature pattern in which the temperature is lowered from the first stage stretching to the final stage stretching with a temperature difference of 2°C or more in each stage of stretching. The lower limit of the number of drawing stages is preferably two or more. When the drawing stage is two or more, the drawing stress can be reduced, and breakage due to foreign matter can be suppressed. The upper limit of the number of drawing stages is preferably 5 or less. When the number of drawing stages is 5 or less, it is possible to prevent the equipment from becoming too large. In addition, when multi-stage stretching is performed, a constant length zone can be appropriately provided after each stretching stage. By providing a constant length zone after each stretching stage, the internal stress generated during stretching can be alleviated in the constant length zone, thereby further reducing the stretching stress when the next stretching is performed, and thus preventing the film from breaking.

[0061] The lower limit of the heat setting temperature is preferably 170° C., more preferably 180° C., and particularly preferably 190° C. If the temperature is 170° C. or higher, the heat shrinkage rate can be reduced. The upper limit of the heat setting temperature is preferably 230° C., more preferably 220° C., and particularly preferably 210° C. When the temperature is 230° C. or lower, the decrease in mechanical strength due to the brittleness of the biaxially oriented polyester film can be suppressed.

[0062] The lower limit of the TD relaxation rate is preferably 0.5%, more preferably 1.0%, and particularly preferably 2.0%. If it is 0.5% or more, the thermal shrinkage rate in the TD direction can be kept low. The upper limit of the TD relaxation rate is preferably 10%, more preferably 8%, and particularly preferably 6%. If it is 10% or less, loosening can be prevented, and flatness can be improved.

[0063] By adopting the above-mentioned preferred film-forming conditions, a long film can be continuously obtained without breakage during the film-forming of a biaxially oriented polyester film containing foreign matter, and the following preferred film properties can be satisfied.

[0064] [Structure and properties of biaxially oriented polyester film] The lower limit of the thickness of the biaxially oriented polyester film of the present invention is preferably 5 μm, more preferably 10 μm, and particularly preferably 15 μm. By making it 5 μm or more, breakage due to foreign matter can be suppressed. The upper limit of the thickness of the biaxially oriented polyester film of the present invention is preferably 100 μm, more preferably 70 μm, and particularly preferably 40 μm.

[0065] The lower limit of the plane orientation coefficient (ΔP) of the biaxially oriented polyester film of the present invention is preferably 0.160, more preferably 0.161, and particularly preferably 0.162. By making it 0.160 or more, the mechanical strength can be kept sufficiently high. The upper limit of ΔP of the biaxially oriented polyester film of the present invention is preferably 0.170, more preferably 0.169, and particularly preferably 0.168. By setting it to 0.170 or less, the stretching stress in the stretching process can be suppressed, and as a result, breakage due to foreign matter in the stretching process can be suppressed.

[0066] The lower limit of the breaking strength in the MD direction of the biaxially oriented polyester film of the present invention is preferably 180 MPa, more preferably 185 MPa, and particularly preferably 190 MPa. If it is 180 MPa or more, the mechanical strength of the bag made into a product is sufficient. The upper limit of the breaking strength in the MD direction of the biaxially oriented polyester film of the present invention is 260 MPa, more preferably 255 MPa, and particularly preferably 250 MPa. When it is 260 MPa or less, breakage caused by foreign matter during the stretching process can be substantially suppressed, and the film formability is good.

[0067] The lower limit of the breaking elongation in the MD direction of the biaxially oriented polyester film of the present invention is preferably 80%, more preferably 90%, and particularly preferably 100%. When it is 80% or more, breaking caused by foreign matter during the stretching process can be substantially suppressed, and the film formability is good. The upper limit of the breaking elongation in the MD direction of the biaxially oriented polyester film of the present invention is 170%, more preferably 160%, and particularly preferably 150%. If it is 170% or less, the mechanical strength of the bag made into a product is sufficient.

[0068] The lower limit of the heat shrinkage rate in the MD direction of the biaxially oriented polyester film of the present invention is preferably 0.5%, more preferably 0.8%, and particularly preferably 1.1%. If it is 0.5% or more, the film becomes brittle, and the decrease in mechanical strength can be suppressed. The upper limit of the heat shrinkage rate in the MD direction of the biaxially oriented polyester film of the present invention is preferably 2.0%, more preferably 1.7%, and particularly preferably 1.4%. When it is 2.0% or less, breakage caused by foreign matter during the stretching process can be substantially suppressed, and the film formability is good.

[0069] The upper limit of the thickness unevenness per 800 mm in the width direction of the biaxially oriented polyester film roll of the present invention is preferably 18%, more preferably 16%, and particularly preferably 14%. When it is 18% or less, the winding quality when made into a roll is good.

[0070] The biaxially oriented polyester film roll of the present invention is 1000 m 2 When there is one or more foreign objects having a maximum length of 1.3 mm or more per 1000 m2, the film is likely to break due to the foreign objects during stretching under conventional film-forming conditions, making stable film-forming difficult. However, by stretching the film under the film-forming conditions described in the present invention so that the heat shrinkage rate and the degree of planar orientation of the film are within the predetermined ranges, stable stretching is possible even in the presence of the foreign objects as described above. On the other hand, the 1000 m of the biaxially oriented polyester film roll of the present invention 2 The lower limit of the number of foreign objects having a maximum length of 1.3 mm or more per unit area is preferably 10 or less. If the number of foreign objects having a maximum length of 1.3 mm or more exceeds 10, defects after printing will increase, which may reduce the yield of the secondary processing step.

[0071] The biaxially oriented polyester film roll of the present invention is 8000m 2The number of foreign objects having a maximum length of 1.0 mm or more per 8000 m2 is 16 or more. When there are 16 or more foreign objects having a maximum length of 1.0 mm or more per 8000 m2, there are many triggers for breakage in a conventional film, making it difficult to produce a long continuous film. However, by stretching the film under the film-forming conditions described in the present invention so that the heat shrinkage rate and the degree of planar orientation of the film are within predetermined ranges, stable stretchability can be ensured even if foreign objects are present as described above, and a long film roll can be obtained. On the other hand, the 8000m of the biaxially oriented polyester film roll of the present invention 2 The upper limit of the number of foreign objects having a maximum length of 1.0 mm or more per unit area is preferably 80 or less. If the number of foreign objects having a maximum length of 1.0 mm or more exceeds 80, defects after printing will increase, which may reduce the yield of the secondary processing step.

[0072] A printed layer may be laminated on the biaxially oriented polyester film of the present invention. As the printing ink for forming the printed layer, water-based and solvent-based resin-containing printing inks can be preferably used. Here, examples of the resin used in the printing ink include acrylic resins, urethane resins, polyester resins, vinyl chloride resins, vinyl acetate copolymer resins, and mixtures thereof. The printing ink may contain known additives such as antistatic agents, light blocking agents, ultraviolet absorbing agents, plasticizers, lubricants, fillers, colorants, stabilizers, lubricants, defoamers, crosslinking agents, antiblocking agents, and antioxidants.

[0073] The printing method for providing the printed layer is not particularly limited, and known printing methods such as offset printing, gravure printing, screen printing, etc. can be used. For drying the solvent after printing, known drying methods such as hot air drying, hot roll drying, infrared drying, etc. can be used.

[0074] The biaxially oriented polyester film of the present invention may be provided with a gas barrier layer such as an inorganic thin film layer or a metal foil, provided that the object of the present invention is not impaired.

[0075] When an inorganic thin film layer is used as a gas barrier layer, the inorganic thin film layer is a thin film made of a metal or an inorganic oxide. There are no particular limitations on the material that forms the inorganic thin film layer as long as it can be made into a thin film, but from the viewpoint of gas barrier properties, inorganic oxides such as aluminum, silicon oxide (silica), aluminum oxide (alumina), and a mixture of silicon oxide and aluminum oxide are preferred. In particular, a composite oxide of silicon oxide and aluminum oxide is preferred from the viewpoint of achieving both flexibility and denseness of the thin film layer.

[0076] In this composite oxide, the mixture ratio of silicon oxide and aluminum oxide is preferably in the range of 20 to 70% Al by mass ratio of the metal content. On the other hand, if it is 70% or less, the inorganic thin film layer can be softened, and the thin film can be prevented from being destroyed during secondary processing such as printing and lamination, resulting in a decrease in gas barrier properties. Note that silicon oxide here refers to SiO and SiO 2 Aluminum oxide is AlO or AlO2. 2 O 3 and mixtures thereof.

[0077] The inorganic thin film layer has a thickness of usually 1 to 100 nm, preferably 5 to 50 nm. When the inorganic thin film layer has a thickness of 1 nm or less, more satisfactory gas barrier properties are easily obtained. On the other hand, when the inorganic thin film layer has a thickness of 100 nm or less, it is advantageous in terms of bending resistance and production costs.

[0078] The method for forming the inorganic thin film layer is not particularly limited, and any known deposition method may be appropriately used, for example, a physical deposition method (PVD method) such as a vacuum deposition method, a sputtering method, or an ion plating method, or a chemical deposition method (CVD method). A typical method for forming an inorganic thin film layer will be described below using a silicon oxide / aluminum oxide-based thin film as an example. For example, when the vacuum deposition method is used, SiO 2 and Al 2 O 3 or a mixture of SiO 2A mixture of ZnO and Al is preferably used. Particles are usually used as the deposition raw material, and in that case, the size of each particle is desirably large enough that the pressure during deposition does not change, and the preferred particle diameter is 1 to 5 mm. Heating can be performed by resistance heating, high-frequency induction heating, electron beam heating, laser heating, or other methods. It is also possible to introduce oxygen, nitrogen, hydrogen, argon, carbon dioxide, water vapor, or other reactive gases as reactive gases, or to employ reactive deposition using ozone addition, ion assist, or other means. Furthermore, the film formation conditions can be changed arbitrarily, such as applying a bias to the deposition target (laminated film to be subjected to deposition), or heating or cooling the deposition target. Such deposition materials, reactive gases, bias, heating and cooling of the deposition target, etc. can be changed in the same way when the sputtering method or CVD method is used. Furthermore, a printing layer may be laminated on the inorganic thin film layer.

[0079] When an inorganic thin film layer is provided on the biaxially oriented polyester film of the present invention, it is preferable to provide a protective layer on the inorganic thin film layer. The gas barrier layer made of metal oxide is not a completely dense film, but has minute defects scattered thereon. By forming a protective layer by applying a specific resin composition for a protective layer described later on the metal oxide layer, the resin in the protective compatible resin composition penetrates into the defective parts of the metal oxide layer, resulting in an effect of stabilizing the gas barrier properties. In addition, by using a material having gas barrier properties for the protective layer itself, the gas barrier performance of the laminated film is also greatly improved.

[0080] Examples of the protective layer include resins such as urethane-based, polyester-based, acrylic-based, titanium-based, isocyanate-based, imine-based, and polybutadiene-based resins to which curing agents such as epoxy-based, isocyanate-based, and melamine-based curing agents have been added. Examples of the solvent used in forming the protective layer include aromatic solvents such as benzene and toluene; alcohol-based solvents such as methanol and ethanol; ketone-based solvents such as acetone and methyl ethyl ketone; ester-based solvents such as ethyl acetate and butyl acetate; and polyhydric alcohol derivatives such as ethylene glycol monomethyl ether.

[0081] The biaxially oriented polyester film of the present invention may be laminated with a layer of another material. As a method for laminating the layer, a method of laminating the layer after the biaxially oriented polyester film is produced, or a method of laminating the layer during the film production can be adopted.

[0082] The biaxially oriented polyester film of the present invention can be used as a packaging material by forming a heat-sealable resin layer (also called a sealant layer) on the biaxially oriented polyester film. The sealant layer is usually formed by extrusion lamination or dry lamination. The thermoplastic copolymer forming the heat-sealable resin layer may be any one that can fully exhibit the sealant adhesiveness, and may be polyethylene resins such as HDPE, LDPE, and LLDPE, polypropylene resins, ethylene-vinyl acetate copolymers, ethylene-α-olefin random copolymers, ionomer resins, etc.

[0083] The sealant layer may be a single layer film or a multilayer film, and may be selected according to the required function. For example, in order to provide moisture resistance, a multilayer film containing a resin such as an ethylene-cyclic olefin copolymer or polymethylpentene may be used. In addition, the sealant layer may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, and a tackifier. The thickness of the sealant layer is preferably from 10 to 100 μm, and more preferably from 20 to 60 μm.

[0084] The lower limit of the roll width of the polyester film roll of the present invention is preferably 400 mm or more, and from the viewpoint of improving productivity in the secondary processing step, it is more preferably 1000 mm or more, and further preferably 1500 mm or more. On the other hand, the upper limit of the width of the polyester film roll of the present invention is preferably 3000 mm or less, and more preferably 2500 mm or less. If the width of the polyester film roll exceeds 3000 mm, handling becomes difficult and the film is prone to wrinkles due to deflection of the roll. The lower limit of the winding length of the polyester film roll of the present invention is preferably 1000 m or more, and from the viewpoint of productivity in the secondary processing step, it is more preferably 2000 m or more, and further preferably 4000 m or more. On the other hand, the lower limit of the winding length of the polyester film roll of the present invention is 100,000 m, preferably 80,000 m, and more preferably 70,000 m. If the length of the polyester film roll exceeds 100,000 m, the weight of the roll becomes large and handling becomes difficult.

[0085] In the polyester film roll of the present invention, a core for winding the film is preferably a paper core, a plastic core, a metal core, or the like, and can be appropriately selected depending on the application. The gap difference in the width direction of the core after removing the film from the polyester film roll of the present invention is preferably 0.5 mm or less. When a paper tube is used as the core, the paper tube is deformed (distorted) due to distortion of the film or natural shrinkage during storage after winding the film. In this case, if the distortion difference of the paper tube in the width direction (gap difference in the width direction) is large, wrinkles will occur on the winding core side of the film roll, which is not preferable. Therefore, the gap difference in the paper tube after removing the film from the film roll is preferably 0.4 mm or less, more preferably 0.3 mm or less.

[0086] In addition, when a paper tube is used as the core of the polyester film roll of the present invention, the flattened pressure resistance of the cardboard core after removing the film from the film roll is preferably 1700 N / 100 mm or more. If the pressure resistance is lower than 1700 N / 100 mm, the cardboard tube will be distorted by the internal stress applied after the film is wound, and wrinkles will occur in the roll core, which is not preferable. The pressure resistance is preferably 1800 N / 100 mm or more, and more preferably 1900 N / 100 mm or more. The higher the pressure resistance, the better. As a means for obtaining a high flattened pressure resistance of the cardboard tube, there are methods such as increasing the thickness of the cardboard tube and using a hard or ultra-hard cardboard tube designed for high strength.

[0087] In addition, in the heat-shrinkable polyester film roll of the present invention, in order to make the gap difference of the paper tube after removing the film from the film roll 0.5 mm or less as described above, it is preferable that the gap difference in the width direction of the paper tube before winding the film used for winding is 0.3 mm or less. If the distortion difference in the paper tube width direction is 0.4 mm or more, the position where the film is distorted when wound is in an oblique direction, which is not preferable because wrinkles (winding core wrinkles) are likely to occur. The gap difference in the width direction of the paper tube is more preferably 0.2 mm or less, and even more preferably 0.1 mm or less. As a means for reducing the gap difference of the paper tube, a paper tube that is hard and difficult to deform due to vibration during transportation, etc. is used, the paper tube is stored in a moisture-proof bag until use so that the paper tube does not absorb moisture and deform, and the paper tube is stored in a room with constant temperature and humidity so that the paper tube does not absorb moisture and deform.

[0088] The average winding hardness in the width direction of the surface layer of the polyester film roll of the present invention is preferably 500 or more and 850 or less. If it is less than 500, the winding state becomes soft and the winding core wrinkles are in a good direction, but the film roll end face is displaced, which is not preferable. If the winding hardness is higher than 850, the winding state becomes hard and wrinkles are likely to occur due to thickness unevenness, which is not preferable. The average winding hardness in the width direction of the surface layer of the film roll is preferably 550 or more and 800 or less, more preferably 600 or more and 750 or less. It is particularly preferable that it is more than 650 and 750 or less. EXAMPLES

[0089] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples.

[0090] [Back pressure increase coefficient of recycled raw materials] The recycled raw material pellets were dried at 135°C for 12 hours, and then extruded at a temperature of 285°C, a filter filtration diameter of 20 μm, a discharge rate of 6 g / min, and a discharge time of 4 hours. The filter back pressure increase coefficient was calculated using the following formula. K = ΔP / (Q / S) Where, K is the filter back pressure increase coefficient, ΔP=P1-P0 P1: Pressure after 4 hours of extrusion (MPa), P0: Pressure at the start of extrusion (MPa), Q: Extrusion discharge rate (kg / hr), S: Filter filtration area (cm 2 )

[0091] [Thickness of biaxially oriented film] The measurement was performed using a dial gauge in accordance with JIS K7130-1999 Method A.

[0092] [Heat shrinkage rate of biaxially oriented film] The thermal shrinkage rate was measured using a dimensional change test method in accordance with JIS-C-2318, except that the test temperature was 150°C and the heating time was 15 minutes.

[0093] [Refractive index of biaxially oriented film] A sample measuring 5 mm in length and 5 mm in width was cut out from the center of the film width. The refractive indexes of the samples in the longitudinal direction (Nx), width direction (Ny), and thickness direction (Nz) were measured using an Abbe refractometer (NAR-1T manufactured by Atago Co., Ltd.) according to JIS K 7142-1996 A method, using sodium D line as a light source and diiodomethane as a contact liquid. The plane orientation coefficient (ΔP) was calculated using the following formula. Plane orientation coefficient (ΔP) = [(Nx + Ny) / 2] - Nz

[0094] [Strength and elongation of biaxially oriented film] In accordance with JIS K 7127, a test sample 15 mm wide and 100 mm long was cut out in the longitudinal direction of the film. The test sample was subjected to a tensile test using a tensile tester (Shimadzu Corporation, Autograph AG-I) with a gauge length of 50 mm and a tensile speed of 200 mm / min. The breaking strength and breaking elongation of the test sample were calculated from the obtained stress-strain curve.

[0095] [Evaluation of film formability of biaxially oriented films] In each Example and Comparative Example, the case where 10,000 m of the film could be continuously produced without breakage during film production was evaluated as ◯, and the case where 10,000 m of the film could not be continuously produced due to breakage was evaluated as ×.

[0096] [Evaluation of foreign matter in biaxially oriented film (1000 square meters)] A film roll with a width of 800 mm and a length of 1250 m (1000 square meters) was rewound using a rewinding machine. During rewinding, the number of defects was counted using a defect detector (FUTEC F MAX MR). The number of defects with the longest part of the defect being 1.3 mm or larger was counted. Less than 1 defect of 1.3 mm or more: C Number of defects of 1.3 mm or more: 1 to 10: A

[0097] [Evaluation of foreign matter in biaxially oriented film (8,000 square meters)] A film roll with a width of 800 mm and a length of 10,000 m (8,000 square meters) was rewound using a rewinding machine. During rewinding, the number of defects was counted using a defect detector (FUTEC F MAX MR). The number of defects with the longest part of the defect being 1.0 mm or more was counted. Number of defects of 1.0 mm or more: 15 or less: C Number of defects of 1.0 mm or more: 16 or more and 80 or less: A

[0098] [Evaluation of thickness unevenness in the width direction] A sample of 800 mm in the width direction and 40 mm in the length direction was taken from the film roll, and the thickness in the width direction was continuously measured at 5 m / sec using a film tester continuous thickness measuring device (manufactured by Fujiwork Co., Ltd.) The maximum thickness during measurement was Tmax., the minimum thickness was Tmin., and the average thickness was Tave. The thickness unevenness in the film width direction was calculated using the following formula. Thickness unevenness = {(Tmax.-Tmin.) / Tave.} x 100(%)

[0099] [Evaluation of filter clogging] In each Example and Comparative Example, when film production was possible for one week continuously without changing the filter, it was rated as ◯, and when the filter became clogged within one week and continuous film production became difficult, it was rated as ×.

[0100] (Polyester A: Mechanically recycled polyester resin derived from PET containers) After washing out foreign matter such as residual contents from the PET container, the flakes were crushed to obtain flakes. The obtained flakes were washed with 3.5 wt% sodium hydroxide solution under stirring at 85°C for 30 minutes at a flake concentration of 10 wt%. After alkaline washing, the flakes were taken out and washed with distilled water under stirring at 25°C for 20 minutes at a flake concentration of 10 wt%. This water washing was repeated two more times by replacing it with distilled water. After washing with water, the flakes were dried, and then 0.10 parts by mass of silica particles with an average particle size of 2.5 μm were added to the flakes. The flakes were then melted in an extruder, and finer foreign matter was filtered out twice using filters with successively smaller opening sizes, and the third time through a filter with the smallest opening size of 50 μm to obtain polyester A. The back pressure rise coefficient of polyester A was 96 MPa / kg·cm 2 It was.

[0101] (Polyester B: Mechanically recycled polyester resin derived from PET containers) Polyester B was obtained in the same manner as polyester A. The back pressure increase coefficient of polyester B was 64 MPa / kg cm 2 It was.

[0102] (Polyester C: Mechanically recycled polyester resin derived from PET containers) Polyester C was obtained in the same manner as polyester A. The back pressure increase coefficient of polyester C was 32 MPa / kg cm 2 It was.

[0103] (Polyester D: Mechanically recycled polyester resin derived from PET containers) Polyester D was obtained in the same manner as polyester A. The back pressure increase coefficient of polyester D was 10 MPa / kg cm 2 It was.

[0104] (Polyester E: Mechanically recycled polyester resin derived from PET containers) Polyester E was obtained in the same manner as polyester A, except that only clean PET containers were used. The back pressure increase coefficient of polyester E was 8 MPa / kg cm 2 It was.

[0105] (Polyester F: Mechanically recycled polyester resin derived from PET containers) Polyester F was obtained in the same manner as polyester A. The back pressure increase coefficient of polyester F was 105 MPa / kg cm 2 It was.

[0106] (Polyester G: Chemically recycled polyester resin derived from PET containers) The chemically recycled polyester resin recycled from PET bottles used in the production of the biaxially oriented polyester film described below was synthesized by the following method. The PET bottles that were collected and sorted were put into a wet grinder, and 1,000 liters of water with 500g of liquid kitchen detergent added was circulated inside the wet grinder while grinding, and metals, sand, glass, and other materials with high specific gravity were precipitated in a gravity separator connected to the grinder, and flakes were taken out from the top layer. These flakes were rinsed with pure water and centrifuged to produce recovered flakes.

[0107] The recovered flakes were melted in a wet state, and 30 kg of the melted flakes were placed in a stirrer-equipped autoclave and charged into a preheated mixture of 150 kg of ethylene glycol and 150 g of zinc acetate dihydrate. After removing fractions with a boiling point lower than that of ethylene glycol, such as water and acetic acid, the mixture was reacted for 4 hours at a temperature of 195-200°C using a reflux condenser.

[0108] After the reaction was completed, the temperature of the contents of the reactor was lowered to 97 to 98° C., and the contents were filtered while still hot to remove suspended matter and precipitates.

[0109] The filtrate after hot filtration was further cooled, and after confirming that the crude BHET was completely dissolved, it was passed through an activated carbon bed at 50 to 51°C and then through an anion / cation exchange mixed bed over 30 minutes for pre-purification treatment.

[0110] The above pre-purified liquid was again charged into the stirring autoclave and heated to distill off excess ethylene glycol at 198°C under normal pressure, to obtain a molten liquid of concentrated BHET.

[0111] The resulting molten liquid of concentrated BHET was allowed to cool naturally while stirring under a nitrogen gas atmosphere, and then removed from the autoclave to obtain a small block of concentrated BHET.

[0112] The block of fine pieces was again heated to 130°C and melted, then fed to a thin-film vacuum evaporator by a metering pump, evaporated, and cooled and condensed to obtain purified BHET.

[0113] The purified BHET was used as a raw material for melt polymerization to obtain chemically recycled polyester resin G with an intrinsic viscosity of 0.696 dl / g. The back pressure increase coefficient of polyester G was 7 MPa / kg cm 2 It was.

[0114] [Example 1] Polyester A was put into the extruder. The resin was melted at 280°C in the extruder, and then the molten resin was passed through a 50 μm filter mesh and then a 100 μm filter mesh. Then, the resin was cast from a T-die at 280°C and adhered to a 10°C cooling roll by electrostatic adhesion to obtain an unstretched sheet. The unstretched sheet was then stretched 3.6 times in the MD direction at a temperature of 115°C. The film immediately after longitudinal stretching was passed through a heating furnace set at 95°C with a hot air heater, and a 3% relaxation treatment was performed in the longitudinal direction using the speed difference between the rolls at the inlet and outlet of the heating furnace. The film was then passed through a tenter and stretched 4.6 times in the TD direction at 120°C, and heat-set for 3 seconds at 210°C and relaxed for 1 second by 5% to obtain a biaxially oriented polyester film with a thickness of 12 μm. The resin composition of the biaxially oriented polyester film and the film-forming conditions are shown in Table 1. The physical properties and evaluation results of the obtained film are also shown in Table 1.

[0115] [Example 2] The relaxation rate immediately after longitudinal stretching was changed to 0%, and the stretching method in the tenter was changed to three-stage stretching, with 1 m constant length regions provided between the first and second stages and between the second and third stages. A biaxially oriented polyester film with a thickness of 12 μm was obtained by film production in the same manner as in Example 1. The physical properties and evaluation results are shown in Table 1.

[0116] [Example 3] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film production in the same manner as in Example 1, except that the relaxation rate immediately after longitudinal stretching was changed to 0% and the stretching pattern in the tenter was changed to a logarithmic form. The stretching angles of the tenter were adjusted to a first stage refraction angle θ1: 12.6°, a second stage refraction angle θ2: 8.2°, and an angle change rate of 34.9%, and the stretching ratio was set so that the total stretching ratio was the same as in Example 1. The physical properties and evaluation results are shown in Table 1.

[0117] [Example 4] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the relaxation rate immediately after the longitudinal stretching was changed to 1%. The physical properties and evaluation results are shown in Table 1.

[0118] Hereinafter, all references to Example 5 shall be read as Reference Example 1. [Example 5] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the relaxation rate immediately after the longitudinal stretching was changed to 10%. The physical properties and evaluation results are shown in Table 1.

[0119] [Example 6] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the longitudinal stretching ratio was changed to 3.9 times. The physical properties and evaluation results are shown in Table 1.

[0120] [Example 7] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the longitudinal stretching ratio was changed to 2.6 times. The physical properties and evaluation results are shown in Table 1.

[0121] [Example 8] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the transverse stretching ratio was changed to 4.9 times. The physical properties and evaluation results are shown in Table 1.

[0122] Hereinafter, all references to Example 9 shall be read as Reference Example 2. [Example 9] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the transverse stretching ratio was changed to 2.6 times. The physical properties and evaluation results are shown in Table 1.

[0123] [Example 10] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the resin was changed to Polyester B. The physical properties and evaluation results are shown in Table 1.

[0124] [Example 11] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the resin was changed to Polyester C. The physical properties and evaluation results are shown in Table 1.

[0125] [Example 12] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the resin was changed to Polyester D. The physical properties and evaluation results are shown in Table 1. [Example 13] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the resin was changed to Polyester G. The physical properties and evaluation results are shown in Table 1.

[0126] [Comparative Example 1] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film production in the same manner as in Example 1, except that the filter mesh through which the molten resin passed was changed to 20 μm and 50 μm and the relaxation rate immediately after the longitudinal stretching was changed to 0%. The filter mesh was clogged, resulting in a defective film.

[0127] [Comparative Example 2] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the filter mesh through which the molten resin passed was changed to 20 μm and 50 μm, the resin was changed to Polyester D, and the relaxation rate immediately after the longitudinal stretching was changed to 0%. The filter mesh was clogged, resulting in a defective film.

[0128] [Comparative Example 3] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the resin was changed to Polyester E and the relaxation rate immediately after longitudinal stretching was set to 0%. The obtained biaxially oriented polyester film had little foreign matter and no clogging of the filter mesh, but since clean PET containers were selected and used as recycled raw materials, the environmental friendliness was insufficient.

[0129] [Comparative Example 4] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the resin was changed to Polyester F and the relaxation rate immediately after the longitudinal stretching was set to 10%. The obtained biaxially oriented polyester film had many breaks due to foreign matter and had poor film formability.

[0130] [Comparative Example 5] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the relaxation rate immediately after the longitudinal stretching was set to 12%. The obtained biaxially oriented polyester film had a low planar orientation coefficient and poor mechanical strength.

[0131] [Comparative Example 6] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the relaxation rate immediately after the longitudinal stretching was set to 0%. The obtained biaxially oriented polyester film had many breaks due to foreign matter, and had poor film formability.

[0132] [Comparative Example 7] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the longitudinal stretching ratio was set to 4.1 times. The obtained biaxially oriented polyester film had many breaks due to foreign matter, and had poor film formability.

[0133] [Comparative Example 8] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the longitudinal stretching ratio was set to 2.3 times. The obtained biaxially oriented polyester film had a low planar orientation coefficient and poor mechanical strength.

[0134] [Comparative Example 9] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the transverse stretching ratio was set to 5.1 times. The obtained biaxially oriented polyester film had many breaks due to foreign matter, and had poor film formability.

[0135] [Comparative Example 10] A biaxially oriented polyester film having a thickness of 12 μm was obtained by film formation in the same manner as in Example 1, except that the transverse stretching ratio was set to 2.3 times. The obtained biaxially oriented polyester film had a low planar orientation coefficient and poor mechanical strength.

[0136] [Table 1A]

[0137] [Table 1B]

[0138] [Table 1C]

[0139] [Table 1D] [Industrial Applicability]

[0140] The biaxially oriented polyester film roll of the present invention has good productivity and can be made into a long film even if the recycled raw materials contain a large amount of foreign matter. It can be widely used in the field of packaging films such as food packaging films. Since there is a strong demand for reducing the environmental load these days, it is expected to make a great contribution to the industrial world.

Claims

1. A biaxially oriented polyethylene terephthalate film roll for packaging, which is made of a polyester resin composition containing recycled raw materials derived from PET bottles, and which is made of polyethylene terephthalate that may contain 10 mol % or less of a component selected from the group consisting of isophthalic acid, naphthalenedicarboxylic acid, 4,4-diphenyldicarboxylic acid, adipic acid, sebacic acid, diethylene glycol, hexamethylene glycol, neopentyl glycol, cyclohexanedimethanol, polyethylene glycol, and polypropylene glycol as a copolymerization component, and which is obtained by winding up a biaxially oriented polyethylene terephthalate film having a thickness of 5 μm or more and 100 μm or less and which satisfies the following (1) to (3) and has a roll length of 1,000 m or more. (1) The heat shrinkage rate in the longitudinal direction of the film when measured at 150° C. for 30 minutes is 0.5% or more and 2.0% or less. (2) The plane orientation coefficient (ΔP) of the film calculated from the refractive index measured based on JIS K 7142-1996 Method A is 0.161 or more and 0.170 or less. (3) 1,000m film roll 2 There is one or more foreign objects with a maximum length of 1.3 mm or more per unit area.

2. The biaxially oriented polyethylene terephthalate film roll for packaging according to claim 1, characterized in that the recycled raw material derived from PET bottles according to claim 1 is a mechanically recycled polyester resin and / or a chemically recycled polyester resin.

3. 3. The biaxially oriented polyethylene terephthalate film roll for packaging according to claim 1, wherein the thickness variation per 800 mm in the film width direction is 18% or less.

4. 4. The biaxially oriented polyethylene terephthalate film roll for packaging according to any one of claims 1 to 3, characterized in that the breaking strength in the longitudinal direction of the film is 180 MPa or more and 260 MPa or less, and the breaking elongation is 80% or more and 170% or less.

5. Film roll 8000m 2 5. The biaxially oriented polyethylene terephthalate film roll for packaging according to any one of claims 1 to 4, characterized in that the number of foreign objects having a maximum length of 1.0 mm or more per roll is 16 or more.

Citation Information

Patent Citations

  • Biaxially oriented polyethylene terephthalate film for protecting polarizer

    JP2012220879A

  • Biaxially-oriented polyester film obtained by using pet bottle-recycled raw material

    JP2014065282A

  • Polyester film for surface protective film of flexible display

    JP2020012087A

  • Biaxially oriented polyethylene terephthalate film roll

    JP2023035545A

  • Method for producing polyester film having furandicarboxylic acid unit

    WO2018159648A1